A construção identitária da marca Riachuelo: uma abordagem semiótica - Gomes, Fernanda Fontanetti (2019)
The speeches built by contemporary fashion brands increasingly transmit values that constitute very important character traits in the creation of their identity. These values, added to the fashion product itself, are decisive for enunciators to feel compelled to look for valuables and opt for one brand over the other because they share the same set of values conveyed by enunciators in their advertising and marketing practices. Today, the senses are built in a sociocultural space permeated by a diversity of digital media that dialogue with each other and make the speed of communication increasingly comprehensive and effective. This ease of integration and interaction modifies the social conditions of apprehension and meaning production, tightening the bonds between enunciator and enunciator. The corpus of this research consists of the actions and advertising campaigns conveyed by the enunciator-Riachuelo in the period between 2017 and 2018, when the enunciator presents the repositioning of the brand through different advertising activities. The present work seeks to investigate how Riachuelo builds its symbolic universe of values and how these values in circulation become preponderant in the decision-making process of fashion consumers. For this, it is based on the discursive semiotics of Algirdas. J. Greimas et al., Drawing on the generative course of meaning to examine the articulations of meanings in discourses, to explain the semi-symbolic relations established in syncretic texts, and to dwell on Eric Landowski's sociosemiotics, to analyze the way the meanings that they are built through interaction regimes. It was observed that the advertising campaigns proposed by the enunciator-Riachuelo syncretize several languages, ratifying the relationship between expression and content as a way to promote values underlying the identity constructions of the enunciators. It is concluded that, through the different regimes of interaction and meaning, it is possible to undertake on which the existential choices of the subjects that determine their ways of being and acting with the world around them are based.